Implementation of Public Consultation in Land Acquisition for the Public Interest on a Small Scale as a Manifestation of the Principle of Transparency in Good Governance: Pelaksanaan Konsultasi Publik dalam Pengadaan Tanah untuk Kepentingan Umum Skala Kecil Sebagai Perwujudan Prinsip Transparansi dalam Good Governance - Syadia, Nadila Audy (Annual Review of Legal Studies, 2024)
This study was raised from the problem of lack of information and unclearness in the certainty of compensation payments in Klidang Lor Village. This study aims to identify and analyze the implementation of public consultation in land acquisition and identify and analyze the implementation of the embodiment of the transparency principle of Good Governance in the implementation of public consultation. This study uses an empirical legal research method with a qualitative approach that uses primary and secondary data sources. Primary data is carried out through observation, interviews, and documentation studies. Data validation uses triangulation, while data analysis is through data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the implementation of public consultation on land acquisition for small-scale public interests in the flood control work of the Sambong River, Batang Regency is in accordance with Law No. 2 of 2012 concerning Land Acquisition for Public Interest Development. In the public consultation, there was one affected resident who still objected and was resolved through mediation. That the implementation of the embodiment of the principle of transparency in public consultation activities is in accordance with the transparency indicator although not yet 100%. In this case, the target of implementing the principle of transparency in Good Governance in providing access to information is still limited to interested parties and has not been publicly accessible to the general public. The conclusion in the implementation of public consultation of affected residents has fully supported the development of flood control of the Sambong River in Batang Regency. Suggestions for the government should be to provide certainty by adding provisions for openness of information on the development process and land acquisition in laws and regulations and providing public access to information.